2018
DOI: 10.1021/acs.inorgchem.8b01806
|View full text |Cite
|
Sign up to set email alerts
|

Click-Derived Triazolylidenes as Chelating Ligands: Achievement of a Neutral and Luminescent Iridium(III)–Triazolide Complex

Abstract: Versatility in the synthesis of triazole derivatives was exploited to obtain convenient mesoionic carbenes working as chelating or cyclometalating ligands for the preparation of cationic or neutral iridium(III) complexes. We present the synthesis and characterization of three new cationic cyclometalating iridium(III) complexes (1-3-BF) and a neutral one (4), equipped with functionalized triazolylidene ligands. All the complexes are obtained in good yields, present irreversible or quasi-reversible oxidation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 83 publications
3
42
0
2
Order By: Relevance
“…The unique reactivity and advantageous electronic features of heterocyclic carbenes, which can be controlled to a large extent through wingtip groups, constituting heteroatoms and backbone functionalization as outlined in Figure 2a, have already been utilized in many fields of chemistry as evidenced by the increased number of publications on the applications of carbenes in the last two decades [50,51]. Beyond the valuable intrinsic properties, another key feature of heterocyclic carbenes is their superior capacity to bind practically to any metal including W [52], Pd [53], Ir [54], Ru [55][56][57], Au [58], Co, Ni, and Cu [59], Fe [60,61], etc., in low-, medium-, and high-oxidation states to generate stable transition metal-carbene complexes. In spite of the handful articles on the synthesis and photo-and electrochemical characterization of carbene-containing ruthenium(II) complexes, which are indeed potential candidates for photoredox catalysis, nevertheless, to the best of our knowledge, only the very recent study by Torres et al [16] demonstrated applied photoredox chemistry with Ru-carbene systems.…”
Section: Introductionmentioning
confidence: 99%
“…The unique reactivity and advantageous electronic features of heterocyclic carbenes, which can be controlled to a large extent through wingtip groups, constituting heteroatoms and backbone functionalization as outlined in Figure 2a, have already been utilized in many fields of chemistry as evidenced by the increased number of publications on the applications of carbenes in the last two decades [50,51]. Beyond the valuable intrinsic properties, another key feature of heterocyclic carbenes is their superior capacity to bind practically to any metal including W [52], Pd [53], Ir [54], Ru [55][56][57], Au [58], Co, Ni, and Cu [59], Fe [60,61], etc., in low-, medium-, and high-oxidation states to generate stable transition metal-carbene complexes. In spite of the handful articles on the synthesis and photo-and electrochemical characterization of carbene-containing ruthenium(II) complexes, which are indeed potential candidates for photoredox catalysis, nevertheless, to the best of our knowledge, only the very recent study by Torres et al [16] demonstrated applied photoredox chemistry with Ru-carbene systems.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, compound 88 displays hypsochromically shifted emission due to the stabilization of the HOMO level exerted by the bis ‐tetrazolate ancillary ligand. In a following study, the same group employed related 1,2,3‐triazolylidene units as ancillary ligand instead ( 89 – 91 ) . The complexes featuring the 2‐pyridyl‐1,2,3‐triazolylidene ( 89 – 91 ) display similar yellow‐orange emission arising from a relatively short‐lived (τ = 207 and 212 ns in deareated CH 2 Cl 2 , respectively) 3 MLCT excited state involving the 4‐pyridyl‐1,2,3‐triazolylidene.…”
Section: Charged Complexesmentioning
confidence: 99%
“…The three compounds emit bright and structured emission in the blue‐green region arising from an excited state most likely localized onto the “[Ir(ppy) 2 ]” scaffold, as demonstrated by the minor effect upon changing the ancillary ligand. Yet, both derivatives featuring the methyl substitution in position 4 of the 1,2,3‐triazole ring (compounds 92 – 93 ) display a PLQY value as high as 0.57 and 0.50, respectively, much higher than those recorded for related compounds where the coordination take place via the 1,2,3‐triazole motif (compounds 95 – 96 ), in accordance with related systems previously reported …”
Section: Charged Complexesmentioning
confidence: 99%
“…[37][38][39][40][41][42] In the past decade, metal complexes of MICs were shown to display excellent properties, among others in homogeneous catalysis, [37][38][39][40][41][42] in redox switchable catalysis, [43][44][45] and in photochemistry. [46][47][48][49][50][51][52][53][54][55] Despite this progress in the development of MICs, the field is almost exclusively dominated by neutral MICs, even though there have been some recent examples of cationic MIC ligands. [43][44][45] To the best of our knowledge, there is just one report on a borate-based anionic MIC compound of the triazolylidene-type (Figure 1, B), [56] which was synthesized from the corresponding 1,5-regioisomer of the triazole.…”
Section: Introductionmentioning
confidence: 99%